Bridging the gap in outpatient care for adolescent eating disorders: Usability of a digital mental health intervention for anorexia or bulimia nervosa - Sanchez Roman, Szarah; Panek, Emily; Niemeyer, Larissa; Saase, Victor; Norden, Matthias; Frenkel, Marie Ottilie (Frontiers in Psychiatry, 2025)
Eating disorders such as Anorexia Nervosa (AN) and Bulimia Nervosa (BN) are serious mental illnesses that typically emerge during adolescence and often become chronic. In Germany, affected individuals wait an average of 26 weeks for outpatient psychotherapy, creating a critical treatment gap. Digital interventions may serve as a bridging solution, particularly for the digitally oriented younger population. This study evaluated the Usability, Acceptance and perceived Usefulness of a cognitive behavioral therapy (CBT)-based mobile intervention for adolescents with AN or BN. Data collection occurred in two phases: an initial pilot with 10 mentally healthy adolescents (mean age = 13.8, SD = 1.2; n_female = 7), followed by a second phase with 20 adolescents (mean age = 14.9, SD = 1.6; n_female = 20) diagnosed with an eating disorder. Assessments included the German Mobile Health App Usability Questionnaire (G-MAUQ) and semi-structured focus group interviews. Qualitative data was analyzed using content analysis according to Kuckartz. On a 1–7 scale, the clinical group and the healthy group reported similar mean usability scores (M = 5.97, SD = 0.44 vs. M = 5.84, SD = 0.44), indicating high usability in both groups. Feedback clustered around four themes: Interface Satisfaction, Feature Acceptance, Ease of Use, and Usefulness. Personalization through companions, gamification, and design were well received. The meal planner was particularly valued for its practical relevance. Focus group interviews highlighted both strengths (e.g., personal approach, interactive format, structured meal planning) and areas for improvement (e.g., text length). Given its scalability, this CBT-based intervention may help fill existing service gaps in the healthcare of adolescents with eating disorders and complement existing treatment pathways.